2019
DOI: 10.1055/s-0039-3400250
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Photon Upconversion by Anionic Acceptors Self-Assembled on Cationic Bilayer Membranes with a Long Triplet Lifetime

Abstract: Anionic 9,10-diphenylanthracene chromophores electrostatically bound to cationic, chiral bilayer membranes show ordered self-assembly in water. The integrity of the chromophore-accumulated aqueous bilayer membranes is ensured by multiple hydrogen-bond networks introduced in the bilayer, which allowed adaptive accommodation of the guest chromophores at the inner surface of the bilayer while maintaining their cohesive interactions. The regular chromophore alignment in the aqueous assembly is confirmed by differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…[14] This strategy was applied for an oxygen tolerant upconversion process. [5,15] Micelles Micelles self-assemble in water due to the amphipilic nature of the surfactants and within different compartments of the micelles, unique microenvironments arise with a number of previously showcased benefits in the context of photochemical reactivity [16] -one of them being an increased oxygen tolerance. [17,18] Hence, the micelle could potentially provide the perfect environment for oxygen sensitive photoreactions to take place.…”
Section: Membranes Bilayer Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] This strategy was applied for an oxygen tolerant upconversion process. [5,15] Micelles Micelles self-assemble in water due to the amphipilic nature of the surfactants and within different compartments of the micelles, unique microenvironments arise with a number of previously showcased benefits in the context of photochemical reactivity [16] -one of them being an increased oxygen tolerance. [17,18] Hence, the micelle could potentially provide the perfect environment for oxygen sensitive photoreactions to take place.…”
Section: Membranes Bilayer Membranesmentioning
confidence: 99%
“…The anionic headgroup of the designed surfactant acts further as a barrier for oxygen and consequently the desired oxygen sensitive photochemical pathway could occur to a satisfactory extent without the need for oxygen removal [14] . This strategy was applied for an oxygen tolerant upconversion process [5,15] …”
Section: Membranesmentioning
confidence: 99%
“…D. Asthana et al reported a lipid-based supramolecular system in which the acceptor arranges itself along the bilayer structure. 74 Lipid structures also helps in solubilizing the donor (PtOEP) which being hydrophobic in nature will have a tendency to get precipitated in water. A mixture of a cationic lipid–anionic acceptor (DPA-SO 3 − ) complex and a PtOEP donor gets easily dispersed in water and exhibits TTA-UC under mild irradiation conditions ( I th = 25 mW cm −2 ).…”
Section: Supramolecular Self-assembly and Photon Up-conversionmentioning
confidence: 99%